Signs of the Time - Elias, Willem (Amsterdam Rodopi, 1997)
Signs of the Time is an investigation into contemporary art theory and the philosophy of art from 1945 till postmodernism. The author treats important precursors such as Freud and Marx, and contemporary theorists and philosophers such as Gombrich, Lacan, Heidegger, Sartre, Althusser, Marcuse, Gadamer, Derrida, Eco, Barthes, Foucault, Baudrillard, and Lyotard. Various texts are discussed, criticized and related to movements in contemporary art and to contemporary artists. The author addresses students in the field of art history, communica-tions, aesthetics, art education, art history, communications, aesthetics, as well as the art lover. Art as a sign of the time reveals the hidden dimensions of the world in which we live.
Keywords: 20th Century (1901-2000); Esthetics